The impact of internal controls on SACCO performance in Rukiga, Uganda - Patience, Kiconco; Moses, Agaba; Bosco, Turyasingura John; David, Kabagambe Jesse (Annals of Management and Organization Research, 2022)
Purpose: The research on the internal controls of Rukiga SACCO was conducted in Rukiga District to examine the segregation of duties, determine the impact of independent checks, and assess the risk management on the financial performance of the organization. Research methodology: This research was carried out after the cross-sectional survey. The bivariate correlations between the predictor components and the dependent variable were examined using a Pearson correlation matrix, and a linear regression model was used to fit the data. Results: The regression model results showed that segregation of duties (R=762), independent checks (R=676), and risk management (R=899) had beneficial influence on Rukiga SACCO performance. Furthermore, the performance was impacted by risk management, separation of roles, and independent checks. Limitations: The structured questionnaire, which was administered by the participant, served as the primary data collection tool. The probability of non-responses occurred due to the loss of control over the questionnaire after submission to respondents. This situation had a significant impact on the data analysis and the generalizability of the findings. Contribution: Task segregation, independent auditing, and risk management should be considered to achieve loan portfolio expansion, profitability development, and market share increase, which were crucial elements of Rukiga SACCO performance.